The SAR Planning ‘P’ Process - Wright, Scott; Smith, Richard (Journal of search & rescue, 2020)
The Planning P is a familiar framework to Emergency Management for transitioning from the Initial Response for a more a formalized, structured response. In this presentation a SAR-specific P framework is proposed that retains the simplicity of the OODA Loop and Six Step Response Process in the Initial Response Period, with a critical decision point to continue as is, or activate the Incident Management Team in a more Formalized response for Second Operational Period and beyond. Each step and the associated Goals, Objectives, Strategies and Tactics will be explored through to the Subject being located, or Search Suspended. Keywords: Planning P, OODA Loop, Six Step Process, Search Management